2010
DOI: 10.1002/pro.370
|View full text |Cite
|
Sign up to set email alerts
|

Urea denatured state ensembles contain extensive secondary structure that is increased in hydrophobic proteins

Abstract: The goal of this article is to gain a better understanding of the denatured state ensemble (DSE) of proteins through an experimental and computational study of their denaturation by urea. Proteins unfold to different extents in urea and the most hydrophobic proteins have the most compact DSE and contain almost as much secondary structure as folded proteins. Proteins that unfold to the greatest extent near pH 7 still contain substantial amounts of secondary structure. At low pH, the DSE expands due to charge-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 102 publications
(127 reference statements)
1
13
0
Order By: Relevance
“…However, the principal cause for the scatter of the data around the identity line is likely to be the denatured state structure. It is known that the compactness of the denatured state depends both on the osmolyte used [12, 40], and on the type of protein [41]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the principal cause for the scatter of the data around the identity line is likely to be the denatured state structure. It is known that the compactness of the denatured state depends both on the osmolyte used [12, 40], and on the type of protein [41]. …”
Section: Resultsmentioning
confidence: 99%
“…More likely, the correct extent of exposure is intermediate between the upper and lower bound models. 62, 63 …”
Section: Discussionmentioning
confidence: 99%
“…63, 94 RNases Sa, T1, and their variants were expressed and purified as described previously. 82, 95, 96 The purity of all proteins was confirmed by SDS PAGE and MALDI-TOF mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD studies have shown that chignolin is also resistant to unfolding, even at 373 K. 45 Proteins with compact denatured state ensembles contain a greater secondary structure content 46, 47 that reduces the number of interactions between protein and denaturant. 48 CLN025 is a stable β-hairpin polypeptide that is composed entirely of secondary structure with no tertiary structure. Therefore, it is not affected by denaturant and does not unfold as would a protein with tertiary structure.…”
Section: Cln025 Is a Stable Polypeptide Model Of Secondary Structurementioning
confidence: 99%